Insights and Strategies for Effective Islamic Marketing in Diverse Cultural Contexts - Waworuntu, Ahmad Yusdarwin; Amri, Andi (Center of Economic Students Journal, 2024)
This study examines the intricacies of Islamic marketing in diverse cultural contexts, focusing on the integration of Islamic principles, cultural sensitivities, and consumer behavior. The purpose is to elucidate the essential elements and challenges of engaging with Muslim consumers effectively. Employing a literature review approach, this research synthesizes insights from various disciplines, including sociology, anthropology, and psychology, to comprehensively understand Islamic marketing dynamics. Findings underscore the significance of aligning marketing strategies with Islamic values and ethics, emphasizing honesty, fairness, and social responsibility. Cultural sensitivity and adaptation emerge as critical factors for resonating with diverse Muslim audiences, highlighting the importance of understanding cultural nuances such as collectivism and family orientation. Moreover, leveraging digital platforms and social media presents new opportunities for enhancing reach and engagement, particularly among younger demographics like Muslim millennials. This research's implications extend to academia and practice, emphasizing the need for multidisciplinary approaches and methodological pluralism in studying Islamic marketing. By addressing challenges such as misconceptions about Islam and leveraging the opportunities presented by cultural diversity, marketers can unlock the full potential of the global Muslim consumer market. This study contributes to greater cultural understanding and engagement in the worldwide marketplace, fostering intercultural dialogue and promoting inclusivity.